PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA BANK RAKYAT INDONESIA CABANG ADISUCIPTO YOGYAKARTA - Hakim Hakim; Selamat Muliadi (Jurnal Manajemen dan Profesional, 2021)
Service quality is a fundamental factor in a company engaged in the service sector, in this case BRI Branch Adisucipto Yogyakarta Cilacap. Customer satisfaction can be seen from each level of service provided massively. The results of this study indicate that the validity and reliability instrument testing for all service variables, Tangibles (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), and Emphaty (x5) has taken care of the provisions. Meanwhile, from the test results the value of 17.157 and F table of 2.47 with a significance of 0.000. Therefore (17.157> 2.47) with a significance value less than 0.05 (sig responsiveness (Responsiveness), guarantee (Assurance) and empathy (Emphaty) to customers at the Kawunagnten Cilacap Branch of BRI Bank.